2007
DOI: 10.1017/s0950268807008588
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pneumococcal disease in New Zealand 1998–2005: capsular serotypes and antimicrobial resistance

Abstract: Isolates from 3903 cases of invasive pneumococcal disease (IPD) were referred to the national reference laboratory over the 8 years, 1998-2005, as part of the laboratory-based surveillance of this disease in New Zealand. All isolates were serotyped and their antimicrobial susceptibility was tested. The incidence of IPD was highest in young children, with an average annual incidence of 100.8/100,000 in infants aged <2 years. There were changes in the prevalence of several of the serotypes during the 8-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…[45] In NZ, a recent independent analysis using similar methodology showed that the incidence of IPD over the period 2002-5 for children aged <2 years of age was about 75 per 100 000, [12,38] which is within the range found in our study (66 per 100 000; 95% CI 55, 77; see table II). The same study showed that this rate was about onethird lower than invasive Sp.…”
Section: Admissionssupporting
confidence: 85%
See 2 more Smart Citations
“…[45] In NZ, a recent independent analysis using similar methodology showed that the incidence of IPD over the period 2002-5 for children aged <2 years of age was about 75 per 100 000, [12,38] which is within the range found in our study (66 per 100 000; 95% CI 55, 77; see table II). The same study showed that this rate was about onethird lower than invasive Sp.…”
Section: Admissionssupporting
confidence: 85%
“…IPD occurred most frequently in children aged <2 years, in whom the average annual incidence was 101 per 100 000, while in all children aged <5 years it was 54.2 per 100 000. [12] Active surveillance in Auckland, NZ's largest city, during 1984-92 revealed significantly higher IPD incidences in Pacific Island and indigenous Māori children. [13] A recent meta-analysis of clinical trials showed that PCV7 reduces IPD from all serotypes by 74% and from vaccine serotypes by 89% in children aged <2 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary (within the past decade) studies have been conducted in selected childhood [49][50][51][52][53][54][55][56][57][58][59] or adult [60][61][62][63][64][65][66] age groups in diverse geographical jurisdictions worldwide. A relatively smaller number of studies have been conducted in entire populations in recent years and these are displayed in Table 2 [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Importantly, most studies investigating serious infections due to S. pneumoniae have included invasive disease (i.e.…”
Section: Specific Aetiologiesmentioning
confidence: 99%
“…New Zealand introduced PCV7 in June 2008 with administration of the first dose at age six weeks, and changed to PCV10 in mid‐2011. Before vaccination, the incidence of IPD in New Zealand children aged less than two years was estimated at 100.8 per 100 000, with up to five childhood deaths per year from IPD . Since 2008, the rate of IPD has decreased 76% in children aged less than five years due to both direct and indirect immunity from PCV .…”
Section: Introductionmentioning
confidence: 99%